STRATEGI GURU DALAM MENERAPKAN KURIKULUM MERDEKA PADA PEMBELAJARAN BAHASA ARAB SISWA KELAS X DI SMA MUHAMMADIYAH 2 SIDOARJO - Qurrota A'yun, Nur Rifdah; Ammar, Farikh Marzuki (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
Teacher strategy has an important role in learning. Therefore, this study examines the teacher's strategy in implementing an merdeka curriculum in Arabic language learning for grade X students at Muhammadiyah 2 Sidoarjo High School. The objectives of this study are, 1) to find out the teacher's strategy in implementing an merdeka curriculum in Arabic language learning for grade X students at Muhammadiyah 2 Sidoarjo High School, 2) to find out the supporting and inhibiting factors. The method used in this research is descriptive qualitative with data collection techniques using interviews, observation and documentation. Data analysis techniques used are reducing data, presenting data that has been collected and drawing conclusions from the data that has been obtained or verification. The results of this study are the Arabic language teacher's strategy in implementing an merdeka curriculum in Arabic language learning for class X students at SMA Muhammadiyah 2 Sidoarjo, there are three teacher strategies, namely 1) lesson planning, 2) lesson implementation and 3) assessment. And the supporting factors consist of independent curriculum workshops, and adequate learning facilities and inhibiting factors consist of adjusting the learning process for students, and lack of interest in learning Arabic